Bussines Intelligent in Telemarketing Using SVM - Ananta Wijaya, Putu Agung; Budiarta, Komang; Sudarma, Made (International Journal of Engineering and Emerging Technology, 2017)
Direct marketing provides an advantage in approaching consumers. Communication that happens allows us more closely, able to change the behavior and know the needs required by consumers accurately. But this technique has a lack of time. It takes a long time to convince consumers to buy the products offered. Bussines intelligent with data mining approach to consumer data is required. This process will analyze the potential possessed by a consumer. At the stage of the DSS used SVM method to predict whether consumers will buy products that have been offered. Bussines intelligent built proven able to predict consumers who have the potential to buy products. Tests show the greatest prediction accuracy rate is 89.5% with a combination of data traning of 70% of the dataset.